Evaluation of the Genetic Variation Spectrum Related to Corneal Dystrophy in a Large Cohort - Li, Wei; Qu, Ning; Li, Jian-Kang; Li, Yu-Xin; Han, Dong-Ming; Chen, Yi-Xi; Tian, Le; Shao, Kang; Yang, Wen; Wang, Zhuo-Shi; Chen, Xuan; Jin, Xiao-Ying; et al. (Frontiers in Cell and Developmental Biology, 2021)
ABSTRACT Aims: To characterize the genetic landscape and mutation spectrum of patients with corneal dystrophies (CDs) in a large Han ethnic Chinese Cohort with inherited eye diseases (IEDs). Methods: Retrospective study. A large IEDs cohort was recruited in this study, including 69 clinically diagnosed CD patients, as well as 8,331 other types of eye diseases and healthy family members as controls. The 792 genes on the Target_Eye_792_V2 chip were used to screen all common inherited eye diseases in our studies, including 22 CD-related genes. Results: We identified 2,334 distinct high-quality variants on 22 CD-related genes in 8,400 individuals. A total of 21 distinct pathogenic or likely pathogenic mutations were identified, and the remaining 2,313 variants in our IED cohort had no evidence of CD-related pathogenicity. Overall, 81.16% (n=56/69) of CDs patients received definite molecular diagnoses, and TGFBI, CHTS6 and SLC4A11 genes respectively covered 91.07%, 7.14% and 1.79% of the diagnosed cases. Twelve distinct disease-associated mutations in the TGFBI gene were identified, 11 of which were previously reported and one is novel. 4 of these TGFBI mutations (p.D123H, p.M502V, p.P501T, p.P501A) were redefined as likely benign in our Han ethnic Chinese IEDs cohort after performing clinical variant interpretation. Among 56 CDs patients with positive detected mutations, the recurrent TGFBI mutations were p.R124H, p.R555W, p.R124C, p.R555Q, p.R124L, and the proportions were 32.14%, 19.64%, 14.29%, 10.71%, and 3.57%, respectively. Twelve distinct pathogenic or likely pathogenic mutations of CHTS6 were detected in 28 individuals. The recurrent mutations were p.Y358H, p.R140X, p.R205W, and the proportions were 25.00%, 21.43%, and 14.29%, respectively. All individuals associated with TGFBI were missense mutations. 74.19% associated with CHTS6 mutations were missense mutations, and 25.81% were nonsense mutations. No de novo mutations were identified. Conclusions: For the first time, our large cohort study systematically described the variation spectrum of 22 CD-related genes and evaluated the frequency and pathogenicity of all 2,334 distinct high-quality variants in our IED cohort of 8,400 individuals. Our research will provide East Asia and other populations with baseline data from a Han ethnic population-specific level. Key Words: Corneal Dystrophy; NGS-Panel; Mutation spectrum; Population-specific level; Baseline data;